Constructions of the literacy competence levels of multilingual students. (3rd September 2017) - Holm, Lars
ABSTRACT: The aim of this article is to examine teachers' constructions of the literacy competence levels of multilingual students. The study is based on a Latour-inspired theoretical understanding of standardised literacy testing as a social practice, and focuses on teachers' perceptions of and practices concerning compulsory national standardised literacy testing in three Danish primary classes containing a number of multilingual students. The analysis reveals that the teachers embed the national standardised tests and their results in a broader competence framework in which a test-based and an everyday-based construction of competence operate side by side in sometimes conflicting ways. The analysis also shows that the teachers' navigation between the two constructions of competence is closely related to central issues in the international academic discourse about the validity of standardised literacy testing of multilingual students. These findings give reason to question and discuss equality-oriented educational programmes and strategies for multilingual students in which standardised literacy testing plays a central role, and to discuss ethical issues around the production and use of standardised literacy tests in educational contexts which are characterised by linguistic diversity.